A stable 1D helical silver coordination polymer with red emission. Issue 21 (8th May 2019) - Li, Yuan; Lu, Shu-Han; Zhao, Rui-dun; Lu, Zhi-Xiang; Liu, Xiao-Lan; Qin, Yu; Yang, Shao-Xiong; Zheng, Li-Yan; Cao, Qiu-e
Abstract : Here, a new 1D helical chain coordination polymer with enhanced chemical stability and fluorescence emission was prepared by introducing a benzimidazole molecule into Ag12 clusters. Abstract : Here, a new 1D helical chain coordination polymer with enhanced chemical stability and fluorescence emission was prepared by introducing a benzimidazole molecule into Ag12 clusters. This coordination polymer demonstrated an increased fluorescence intensity with increasing polarity of alcohol solution, revealing its potential application in alcohol sensing.